Implementasi Metode Task Based Language Learning untuk Meningkatkan Kompetensi Bahasa Inggris Berbasis Android - Fadhil Ahmad; Tata Sutabri (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
This study explores the implementation of Task-Based Language Learning (TBLL) in developing an Android-based application to enhance English language proficiency. TBLL was chosen for its focus on real-world language usage, enabling users to practice English skills through practical tasks. The application is developed using the Flutter framework, which supports cross-platform functionality, providing ease of access for users. The study measures the improvement in English language proficiency without relying on surveys for data collection; instead, it uses performance data from users' in-app activities. The findings are expected to demonstrate that integrating TBLL into a digital platform can effectively enhance English proficiency, especially in practical communication skills. This Android-based application implementation is envisioned as an innovative solution for flexible and efficient language learning.